Microbial Antigen-Presenting Extracellular Vesicles Derived from Genetically Modified Tumor Cells Promote Antitumor Activity of Dendritic Cells - Tomoko Ito; Kikuya Sugiura; Aya Hasegawa; Wakana Ouchi; Takayuki Yoshimoto; Izuru Mizoguchi; Toshio Inaba; Katsuyuki Hamada; Masazumi Eriguchi; Yoshiyuki Koyama (MDPI AG, 2021)
Tumor-derived extracellular vesicles (EVs), as tumor vaccines, carry tumor-associated antigens (TAAs), and were expected to transfer TAAs to antigen-presenting cells. However, treatment with tumor-derived EVs exhibited no obvious antitumor effect on the established tumors, likely due to their immuno-suppressive functions, and also to the poor immunogenicity of TAAs. In order to improve the immune stimulating properties, EVs expressing a highly immunogenic bacterial antigen, 6 kDa early secretory antigenic target (ESAT-6), from Mycobacterium tuberculosis were prepared by genetically modifying the parent tumor cells with a plasmid coding for ESAT-6. Cultured B16 tumor cells were transfected with a ternary complex system consisting of pDNA, polyethylenimine (PEI), and chondroitin sulfate. The cells that were transfected with the ternary complex secreted EVs with a higher number of ESAT-6 epitopes than those transfected by a conventional DNA/PEI binary complex, due to the low cytotoxicity, and durable high expression efficiency of the ternary complex systems. The EVs presenting the ESAT-6 epitope (ESAT-EV) were collected and explored as immune modulatory agents. Dendritic cells (DCs) were differentiated from mouse bone marrow cells and incubated with ESAT-EV. After incubating with the EVs for one day, the DCs expressed a significantly higher level of DC maturation marker, CD86. The DCs treated with ESAT-EV showed a significantly improved antitumor activity in tumor-bearing mice.